Labour market areas and cluster subdivision for Spain 2011 - Lucas Martínez-Bernabéu; José Manuel Casado Díaz (REGION, 2022)
Labour market areas (LMAs) are a type of functional areas that provides the appropriate framework for spatially-explicit analyses of the labour market to guide policymaking in this field. This resource presents a data base with the most recent definition of LMAs for Spain using a state-of-the-art methodology. All defined LMAs are highly self-contained in terms of travel-to-work flows and exceed a minimum size compatible with the usual requirements in terms of confidentiality and representativeness, allowing the recoding of microdata geographic referencing and therefore a much greater granularity compared to what is usual for this type of data. It can be downloaded from https://rua.ua.es/dspace/handle/10045/121236.
Keywords: 330